Local variability in the timing and intensity of tropical dry forest deciduousness is explained by differences in forest stand age. Issue 3 (4th May 2018) - Cuba, Nicholas; Lawrence, Deborah; Rogan, John; Williams, Christopher A.
Abstract : Tropical Dry Forest deciduousness is a behavioral response to climate conditions that determines ecosystem-level carbon uptake, energy flux, and habitat conditions. It is regulated by factors related to stand age, and landscape scale variability in deciduous phenology may affect ecosystem functioning in forests throughout the tropics. This study determines whether observed phenological differences are explainable by forest age in the southern Yucatán Peninsula in Mexico, where forest clearing for shifting cultivation has created a mosaic of forest stands of varying age. Matched-pair statistical tests compare neighboring forest pixels of different age class (12–22 years versus 22+ years) and detect significant differences in Moderate Resolution Imaging Spectroradiometer (MODIS) Enhanced Vegetation Index (EVI)-derived metrics related to the timing and intensity of deciduousness during three dry seasons (2008–2011). In all seasons, young forests exhibit significantly more intense deciduousness, measured as total seasonal change of EVI normalized by annual maximum EVI ( p  < 0.001), and larger normalized EVI change during successive dry season months relative to start-of-dry-season EVI ( p  < 0.001), than neighboring older forests subject to similar environmental conditions.